2012
DOI: 10.3767/003158512x660562
|View full text |Cite
|
Sign up to set email alerts
|

Soral synapomorphies are significant for the systematics of the <I>Ustilago-Sporisorium-Macalpinomyces</I> complex (<I>Ustilaginaceae</I>)

Abstract: The genera Ustilago, Sporisorium and Macalpinomyces are a polyphyletic complex of plant pathogenic fungi. The four main morphological characters used to define these genera have been considered homoplasious and not useful for resolving the complex. This study re-evaluates character homology and discusses the use of these characters for defining monophyletic groups recovered from a reconstructed phylogeny using four nuclear loci. Generic delimitation of smut fungi based on their hosts is also discussed as a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 35 publications
5
61
0
Order By: Relevance
“…Molecular phylogenetic studies by Stoll et al (2003Stoll et al ( , 2005 revealed that Sporisorium species are split into two main lineages. This finding was later confirmed by other molecular analyses (Cunnington et al 2005;Vánky et al 2006;Vánky and Lutz 2011;McTaggart et al 2012a;Shivas et al 2013;Zhang et al 2013). These two main lineages included the type species of Sporisorium (S. sorghi Ehrenb.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Molecular phylogenetic studies by Stoll et al (2003Stoll et al ( , 2005 revealed that Sporisorium species are split into two main lineages. This finding was later confirmed by other molecular analyses (Cunnington et al 2005;Vánky et al 2006;Vánky and Lutz 2011;McTaggart et al 2012a;Shivas et al 2013;Zhang et al 2013). These two main lineages included the type species of Sporisorium (S. sorghi Ehrenb.…”
Section: Introductionsupporting
confidence: 73%
“…Sporisorium nervosum AY740057/ AY740110 generated from specimen M 56622 (Stoll et al 2005) may also be wrongly identified, as a sequence of this species (HQ013106), generated from the holotype specimen (BRIP 27019), was nested within the Sporisorium s. str. lineage (McTaggart et al 2012a). Re-sequencing of both specimens is necessary to resolve which sequences are indeed linked to Sporisorium nervosum.…”
Section: Phylogenetic Framework For Anthracocystismentioning
confidence: 99%
“…Spore germination resulted in phragmobasidia that produced basidiospores laterally and terminally. Th e establishment of Anomalomyces as a distinct genus was subsequently supported by molecular analyses (McTaggart et al 2012b). Anomalomyces is monotypic represented by the type species A. panici Vánky, R.G.…”
Section: Introductionmentioning
confidence: 86%
“…1) (Stoll et al 2005;McTaggart et al 2012b). Alignments of sequence data were undertaken with the MAFFT algorithm and were unedited (Katoh et al 2009).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Th e sori are without columella and fi lled with spore balls formed from coiled sporogenous hyphae. Usually, sterile cells formed from non-sporogenous hyphae are absent (McTaggart et al 2012a, b;Vánky 2013 .…”
Section: Introductionmentioning
confidence: 99%